The Use of E-Portfolio for Improving Students’ English Skills: A Pilot Study in English Department, The State Polytechnic of Padang - Dhini Aulia; Desi Yulastri; Witri Handayani (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2016)
ne"> This research addresses the use of technology, especially information technology, by promoting the use of electronicportfolio (e-portfolio) for improving students' English skills. Some experts have suggested the use of e-portfolio for students inindependent learning activities and others proposed this as one of alternative assessment tools. Barret (2005) defines e-portfolio as thestore to collect and organize portfolio artifacts in many types of electronic media such as audio, video, graphic, and text; it usuallyuses hypertext links to manage the materials, connect evidence to appropriate outcomes, goals or standards. However, the term of eportfolio has not been popular among English teachers in Indonesia, especially in English Department of the State Polytechnic ofPadang, although some lecturers in this institution have been using social media in giving instructions, collecting assignments andgiving feedback to students. Moodle LMS has been applied as a platform for the e-portfolio in this research. This research examineswhether the use of e-portfolio improves students’ English skills. The English skills include four skills: Listening, Reading, Speaking,and Writing. An experimental research design will be employed. More specifically, this article discusses the students’ responsestoward the use of Moodle LMS in their learning. The questionnaire was distributed to students to find out their perceptions aboutMoodle LMS. It was found that 64.62% of the responses indicates positive perceptions. In other words, the students gave positiveresponses to the use of Moodle LMS. It can be concluded that Moodle LMS is considered to be used supporting the use of e-Portfolioin the next main study, which will be conducted as an experimental study.